2013
DOI: 10.1002/smll.201202732
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle Exposure Attenuates the Viability of Rat Cerebellum Granule Cells through Apoptosis Coupled to Oxidative Stress

Abstract: The impact of silver nanoparticles (AgNPs) on the central nervous system is a topic with mounting interest and concern and the facts remain elusive. In the current study, the neurotoxicity of commercial AgNPs to rat cerebellum granule cells (CGCs) and the corresponding molecular mechanism are closely investigated. It is demonstrated that AgNPs induce significant cellular toxicity to CGCs in a dose-dependent manner without damaging the cell membrane. Flow cytometry analysis with the Annexin V/propidium iodide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 74 publications
5
73
0
Order By: Relevance
“…In a study on juvenile Japanese medaka (Oryzias latipes), Chae et al (2009) found that AgNPs showed higher toxicity than ionic silver after 24-and 96-h exposures. Similar result was also observed in primary granule cells in vitro (Yin et al, 2013). Moreover, some other metal nanoparticles like gold nanoparticles may not release metal ions, but caused deleterious biological effects through the induction of oxidative stress (Siddiqi et al, 2012), which hinted the particle-specific effects.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In a study on juvenile Japanese medaka (Oryzias latipes), Chae et al (2009) found that AgNPs showed higher toxicity than ionic silver after 24-and 96-h exposures. Similar result was also observed in primary granule cells in vitro (Yin et al, 2013). Moreover, some other metal nanoparticles like gold nanoparticles may not release metal ions, but caused deleterious biological effects through the induction of oxidative stress (Siddiqi et al, 2012), which hinted the particle-specific effects.…”
Section: Discussionsupporting
confidence: 76%
“…Using primary cultures of rat cerebellar granule cells (CGCs), the researchers observed that AgNPs incubation caused excitotoxicity in cultured neurons via activation of N-methyl-D-aspartate (NMDA) receptor, followed by calcium imbalance, mitochondrial dysfunction and reactive oxygen species (ROS) production (ZiemiƄ ska et al, 2014). Significant cellular toxicity in CGCs induced by AgNPs was mediated through programmed cell death coupled to oxidative stress (Yin et al, 2013). These proofs obtained from in vivo and in vitro tests provide the clues on how AgNPs directly interact with neurons and cause the deleterious effects.…”
mentioning
confidence: 99%
“…The primary cultured cerebellum granule cells (CGCs) were prepared according to the protocol reported previously (Yin et al, 2013). Briefly, the cerebellum granule cells dissociated from 7-dayold SD rat pups were plated in 6-well plates (1 Â10 6 cells/mL) precoated with poly-L-lysine (0.01%, Sigma-Aldrich, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Mounting evidences have given some important clues to pathogenic mechanisms in cerebellum ataxia, such as disruption of voltage-gated potassium and calcium channels (Jen et al, 2007;Mori et al, 1991). Our previous study found that AgNPs exposure could attenuate the viability of rat cerebellum granule cells (CGCs) through apoptosis (Yin et al, 2013). Consequently, uncovering in vivo neurological deficits induced by AgNPs and understanding the underlying mechanism are of much significance for finding out the solution to their potential harmful effects.…”
Section: Introductionmentioning
confidence: 99%
“…As published before, nanoparticle exposure attenuates granule cell viability in vitro and in vivo, showing the vulnerability of the population. [54][55][56] Based on the result that VSOP-R2 treatment altered DG viability during long-term incubation, we hypothesize that VSOP-R2 caused oxidative stress and induced apoptosis ( Figure 2X). Because of the outcome of the aforementioned neuron-glia co-culture experiment, we assume protective effects by microglia in OHSC.…”
mentioning
confidence: 99%